The Evaluation of End Tidal Carbon Dioxide Values in Intubated Patients with COVID-19: End Tidal Carbon Dioxide and COVID-19 - Karaali, Rezan; Çakır, Adem; Bora, Ejder Saylav; Akyol, Pınar Yeşim; Kavalcı, Cemil; Acar, Hüseyin (Acta Biomedica Atenei Parmensis, 2022)
Background: The aim of this study is to establish the value of PETCO2 in COVID-19 patients intubated in emergency department, and its effects on mortality. Objectives: Between May 15, 2020 and January 15, 2021, The patients aged ≥18 years and diagnosed COVID-19, scheduled for urgent intubation in the emergency department were included.Method: Single-center, prospective and observational study. Age, gender, vital signs, laboratory findings are recorded. Immediately after intubation as measured by the capnography, the initial PETCO2_1 and at post-ventilation 15 min, PETCO2_2 and first, second arterial blood gas analysis are recorded.Results: The mean age of the 48 patients was 74 years. The PETCO2_1 and PETCO2_2 measurements were statistically significantly different between the patients who survived and those who died (p=0.014, p=0.015). The patients with a high first PETCO2_1 value and a decrease to the normal level survived, but those with a low PETCO2_1 value that could not increase to a normal value died (p=0.038, p=0.031). Increased levels of SpO2, PETCO2_1, PETCO2_2 and PaCO2_2 decreased the risk of mortality, while an increased level of PaO2_2 increased the risk of mortality.Conclusion: Capnography is non-invasive and provides continuous measurement. Assessment of changes in PETCO2 value would contribute to patient survival.